2007
DOI: 10.1080/00365520701206738
|View full text |Cite
|
Sign up to set email alerts
|

Screening for human cationic trypsinogen (PRSS1) and trypsinogen inhibitor gene (SPINK1) mutations in a Finnish family with hereditary pancreatitis

Abstract: In the investigated Finnish pedigree with HP, the PRSS1 mutation R122H is linked with chronic disease. Although the SPINK1 mutation (N34S) was also observed in two individuals, it was not linked with the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The frequency of this pancreatitis reason is described in the literature at the level of 2.5–9.8% [ 9 , 17 ] In 2012, the Sultan showed a high prevalence of genetic mutations (in the SPINK, PRSS1, and CFTR genes) in patients with recurrent and chronic pancreatitis without other causes of these diseases (anatomic and metabolic) [ 18 ]. It is known that mutations in the gene PRSS1 (two types: R122H and N29I) are responsible for hereditary pancreatitis, and SPINK1 gene mutation is strongly associated (about 20% of patients) with idiopathic chronic pancreatitis in children and adolescents [ 19 ]. In recent years, some other mutations associated with the early occurrence of acute and chronic pancreatitis have been described – mutations in the CPA1 gene encoding carboxypeptidase A1 (one of the pancreatic metalloproteinases) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of this pancreatitis reason is described in the literature at the level of 2.5–9.8% [ 9 , 17 ] In 2012, the Sultan showed a high prevalence of genetic mutations (in the SPINK, PRSS1, and CFTR genes) in patients with recurrent and chronic pancreatitis without other causes of these diseases (anatomic and metabolic) [ 18 ]. It is known that mutations in the gene PRSS1 (two types: R122H and N29I) are responsible for hereditary pancreatitis, and SPINK1 gene mutation is strongly associated (about 20% of patients) with idiopathic chronic pancreatitis in children and adolescents [ 19 ]. In recent years, some other mutations associated with the early occurrence of acute and chronic pancreatitis have been described – mutations in the CPA1 gene encoding carboxypeptidase A1 (one of the pancreatic metalloproteinases) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent SPINK1 mutation is p.N34S. Several other mutations, including p.M1, p.L14P, p.L14R, c.[1-215G>A;194+2T>C] and p.R67C, are possibly associated with chronic pancreatitis [3,14,23,24,25,26]. More recent contributions have confirmed the strong association between SPINK1 and CFTR [27,28].…”
Section: Introductionmentioning
confidence: 86%
“…In 1996, Whitcomb et al [7] identified the first mutation associated with hereditary pancreatitis, namely the R122H mutation in the cationic trypsinogen gene (PRSS1). Several other mutations (A16V, K23R, N29I, N29T, R122C) and triplication as well as duplication of the PRSS1 locus have been subsequently described [4,12,13,14,15,16,17,18]. …”
Section: Introductionmentioning
confidence: 99%
“…(8,9) About 100 families have been documented worldwide. (4) which has been screened in different countries (3,(10)(11)(12)(13)(14)(15)(16) HP is a progressive inflammatory disease in which pancreatic secretory parenchyma is destroyed and replaced by fibrous tissue (17), eventually leading to malnutrition and diabetes. (18) several studies shows that, Patients with HP have a markedly increased risk of pancreatic cancer compared with the general population up to 40-50% .…”
Section: Introductionmentioning
confidence: 99%